When Charisma Doesn't Fail: Charismatic Authority and Dissonance Management in the Case of Diamond Mountain - Immergut, Matthew (Interdisciplinary journal of research on religion, 2014)
How do the faithful keep their faith when their spiritual leaders say one thing but then do some- thing else? How do they manage the dissonance that such contradictory behavior evokes? In this article, I examine these questions through a case study of Diamond Mountain, a convert Buddhist community under the charismatic leadership of Geshe Michael Roach and Lama Christie McNally. Drawing on previous scholarly work on failed prophecy, I analyze the rationalizations that members use in the face of less dramatic but more frequent occurrences of leader-induced dissonance. Three prominent rationalizations found in the failed prophecy literature aligned with the rationalizations used by students of Roach and McNally in managing ongoing tensions. The last of these, 'test of faith,' also provides a way to understand how dissonance, confusion, and chaos are not so much deflected by the community but interpreted as a necessary part of the spiritual path. These rationalizations are examined not in isolation but in the context of a broad set of beliefs and group social dynamics.